Piezoelectricity of nano-SiO2/PVDF composite film. (31st August 2018) - Yangzhou, Zhao; Weifeng, Yuan; Chaoyang, Zhao; Bin, Gu; Ning, Hu
Abstract: In this work, a fabrication process was developed to incorporate nano-SiO2 particles into poly(vinylidene fluoride) to make piezoelectric films. Experimental tests show that the piezoelectricity of the nanocomposites can be improved if the weight fraction of the additive increases within a specific range. Optical microscope images indicate that the presence of SiO2 particles can reduce the average diameter of the spherulites and increase the amount of heterogeneous nucleation sites in the PVDF matrix. In the fabrication process, stretching is used to enhance the α-β -phase transformation and orient the dipoles of the β -phase. From the experiment in which the nanocomposite films were affixed onto a vibrating beam for electricity harvesting, it was found that the output voltages of the films are dependent on not only the amplitude but also the frequency of the beam's vibration. This finding may have great potential in the field of energy harvesting using flexible piezoelectric films.